An 18-year-old girl with retrosternal burning discomfort: a bitter pill to swallow - Debbie L Shawcross; Mahmoud Gouda; Ayman Elkholi; Thomas H Tranah (BMJ Open Gastroenterology)
Caustic injury secondary to impaction of ingested batteries is a potentially severe cause of oesophageal injury with an increasing incidence that reflects consumer trends and the utilisation of compact electronic devices. Delays to recognition and management are associated with increased risk of complications, morbidity and mortality. In this manuscript, we describe a case presentation and literature review of a patient presenting with upper oesophageal odynophagia after the deliberate ingestion of multiple foreign bodies.